2005
DOI: 10.1152/jn.00230.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Processing of Noxious Colonic Input by Thoracolumbar and Lumbosacral Dorsal Horn Neurons in the Rat

Abstract: Wang, Gexin, Bin Tang, and Richard J. Traub. Differential processing of noxious colonic input by thoracolumbar and lumbosacral dorsal horn neurons in the rat. J Neurophysiol 94: 3788 -3794, 2005. First published August 10, 2005; doi:10.1152/jn.00230.2005. Previous studies suggest the lumbosacral (LS) spinal cord processes acute colorectal stimuli whereas the thoracolumbar (TL) and LS spinal segments process inflammatory stimuli. In this study, the effects of colorectal distention (CRD) on TL and LS dorsal horn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 39 publications
6
47
2
Order By: Relevance
“…These findings are supported by evidence in the mouse that the PN pathway contains a significantly larger proportion of stretch-sensitive afferents (44% compared with 10% in the LSN) (5), which encodes colorectal distension to drive the visceromotor response, a reliable and widely accepted metric of evoked visceral nociception and hypersensitivity (11,20,25,26). It has been suggested that LSN input assumes a role in colorectal nociception in the presence of inflammation (39).…”
Section: Discussionmentioning
confidence: 72%
“…These findings are supported by evidence in the mouse that the PN pathway contains a significantly larger proportion of stretch-sensitive afferents (44% compared with 10% in the LSN) (5), which encodes colorectal distension to drive the visceromotor response, a reliable and widely accepted metric of evoked visceral nociception and hypersensitivity (11,20,25,26). It has been suggested that LSN input assumes a role in colorectal nociception in the presence of inflammation (39).…”
Section: Discussionmentioning
confidence: 72%
“…There is an increase in the discharge of TL dorsal horn neurons, an increase in CRD-induced Fos expression and the TL dorsal horn contributes to behavioral responses to CRD 7,9,10 . These data are similar to the present observations following acute neurectomy or spinal cold block/transection although the experimental manipulations are in opposite directions (increasing or decreasing colonic input to the LS dorsal horn).…”
Section: Clinical Significancementioning
confidence: 99%
“…It has been shown that colorectal inflammation with turpentine (1 h-48 h) in spinalized rats increases spontaneous activity and CRD-evoked responses in sustained neurons, whereas abrupt neurons have decreased spontaneous activity and CRD-evoked responses [10]. Similar observations in lumbosacral spinal neurons are observed in rats with mustard oil applied in the colon for 30 min to 4 h [12]. It is believed that selective alterations in central inhibitory mechanisms contribute to inflammation-induced increases in reflex responses to CRD.…”
Section: Sl-e and Ll-e Responses To Crdmentioning
confidence: 56%
“…For example, in intact or hormonally modulated female rats, colonic inflammation facilitates the response of abrupt neurons, but does not affect sustained neurons [13]. Cold block of the spinal cord causes abrupt neurons to develop an afterdischarge similar to that of sustained neurons [12]. Furthermore, in primary central sensitization induced by corticosterone implanted in the amygdala but in the absence of colonic inflammation, increased responsiveness to CRD is observed in both the SL-E and the LL-E groups of lumbosacral neurons [24].…”
Section: Sl-e and Ll-e Responses To Crdmentioning
confidence: 99%
See 1 more Smart Citation